1990
DOI: 10.1093/infdis/161.3.430
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Soluble CD16 Levels in Serum of HIV-Infected Patients: Correlation with Clinical and Biologic Prognostic Factors

Abstract: The modulation of soluble CD16 titers in human immunodeficiency virus (HIV)-infected patients' serum, with an initial increase in Centers for Disease Control (CDC) clinical stage II and III patients followed by a dramatic drop in patients with AIDS (CDC clinical stage IV), is reported. These changes are statistically correlated with the CDC staging system, the number of CD4+ cells, the amount of p24 antigen in serum, and the anti-p24 antibody titers, indicating the potential value of soluble CD16 titer as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…We found that sCD16 levels were greatly decreased in sera of patients as compared with healthy HIV-seronegative controls ( p ϭ 0.0001), confirming previous observations (33). The decrease in serum sCD16 levels was a surrogate marker for the progression of HIV disease.…”
Section: Figure 8 Effect Of Rantes and Scd16 On Infection Of Monocytsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that sCD16 levels were greatly decreased in sera of patients as compared with healthy HIV-seronegative controls ( p ϭ 0.0001), confirming previous observations (33). The decrease in serum sCD16 levels was a surrogate marker for the progression of HIV disease.…”
Section: Figure 8 Effect Of Rantes and Scd16 On Infection Of Monocytsupporting
confidence: 90%
“…Thus, it is conceivable that rsCD16, already proposed as a therapeutic agent for acute immune thrombocytopenic purpura (37) and multiple myeloma (33), may be introduced in the group of immunomodulatory drugs for HIV disease, through its ability to restrict the dissemination of HIV infection of CR3-expressing target cells.…”
Section: Figure 8 Effect Of Rantes and Scd16 On Infection Of Monocytmentioning
confidence: 99%
“…In addition to studies investigating alterations in NK cell phenotype during HIV infection, Fig. 4 soluble CD16 is detected in the sera of HIV-infected donors and correlates with disease progression [28]. This observation suggests that the activation-induced cleavage of CD16 may result in a serological marker that associates with HIV disease progression, further suggesting a linkage between chronic NK cell activation and HIV disease progression.…”
Section: Discussionmentioning
confidence: 87%
“…[53][54][55] Of interest, another Mac-1 ligand, soluble CD16 (sCD16), was reported to be significantly decreased in HIV disease progression. 53,56 In addition, intercellular adhesion molecule-1, a ligand of Mac-1, is incorporated into the virion envelope. 57 A confounding aspect of the role of Mac-1 in HIV replication is the observation that ligation of the ␤ 2 integrin chain CD18 by immobilized Ab has been shown to increase HIV transcriptional activation in THP1 monocytic cells.…”
Section: Discussionmentioning
confidence: 99%